EU-Ukraine DCFTA: The model for eastern partnership regional trade cooperation - Veronika Movchan; Volodymyr Shportyuk (Center for Social and Economic Research (CASE), 2012)
The EU has been one of the largest trade partners for so called Eastern Partnership (EaP) countries, namely Armenia, Azerbaijan, Belarus, Georgia, Moldova and Ukraine. Commodity turnover of these countries with the EU vary between 30% and 50% of total, but their access to the EU market is less preferential than for many other neighboring countries. They trade with the EU on the basis of MFN regime, and five EaP countries, with exemption of Belarus, use privileges provided by Generalized System of Preferences (GSP) or the GSP+ or autonomous trade preferences (Moldova). With the launch of EaP initiative in 2009, relations between the EU and the Eastern European countries (Armenia, Azerbaijan, Belarus, Georgia, Moldova and Ukraine) have received new impetus for development. The EaP offers upgrade of relations within three major dimensions, namely (a) the Association Agreement (AA), (b) Agreement on a Deep and Comprehensive Free Trade Area (DCFTA), and (c) Visa Facilitation and Readmission agreements.The AA talks have been launched with all EaP countries expect for Belarus, and four of them have been involved in the DCFTA talks. Ukraine has progressed the most, as after five years of negotiations the EU-Ukraine Association Agreement with embedded DCFTA has been initialed in 2012.The aim of this study is to assess gains and losses that could arise from the DCFTA with the EU for the EaP countries, using information about EU-Ukraine DCFTA as model case for EaP regional trade cooperation.The focus of the paper is on non-tariff (regulatory) component of the EU DCFTA and potential implications of regulatory approximation. Also, current level of harmonization of EaP countries' regulatory framework with the EU acquis in the areas related to the DCFTA is analyzed.
Keywords: F15; 330; EaP; DCFTA; Regional Integration; Ukraine; Internationale Wirtschaftsbeziehungen; EU-Nachbarstaaten; Internationale Zusammenarbeit; Freihandelszone; Handelspräferenzen; Assoziierung; EU-Staaten; Ukraine; Osteuropa